Pendampingan UMKM Melalui Brand Equity Sebagai Upaya Peningkatan Volume Penjualan Di Desa Bareng - Cintia Nur Halimatussa’diyah; Sonja Andarini (STIPAS Tahasak Danum Pambelum Keuskupan Palangkaraya, 2023)
The monetary crisis in 1997 - 1998 is a history that will serve as a lesson for the Indonesian economy. The cause of the monetary crisis was caused by the decline in the value of the rupiah currency, Indonesia's high debt abroad, the price of goods and services became higher and lasted longer, causing inflation. The impact of the monetary crisis was that many companies went bankrupt, banks experienced bad credit, and so on. MSMEs (Micro, Small and Medium Enterprises) became a savior during the 1998 monetary crisis, at that time. MSMEs support the Indonesian economy by surviving and keeping the wheels of the country's economy from the threat of high unemployment. MSMEs have a very important role for Indonesia, because they contribute to gross domestic product and employment. Bareng Village, Bareng District, Jombang Regency is a village that has many MSMEs, and this research discusses brand equity, where branding is still the main obstacle for MSMEs. By making logos and brand names that come from information from MSMEs actors, researchers can assist in assisting with direct understanding and creation. Brand equity is able to increase consumer loyalty and strengthen the brand and can be remembered so that it helps in competing with competitors. Regarding this matter, it has the potential for product placement (positioning) so that consumers understand product quality. Thus sales of MSMEs products will increase and be more advanced than before.